Examination of fingernail contents of Students at The Inpres Yoka Public Elementary School in Jayapura City, Papua - Sinaga, Herlando; Rampa, Ester; Butiti, Lisa Chorani (Poltekkes Kemenkes Mataram, 2025)
One environmental disease that is a public health concern is worm infection. Soil-transmitted helminths (STH) are a type of worm infection caused by various types of intestinal worms that spread through the soil. The purpose of this study was to determine the presence or absence of intestinal worm eggs in nail clippings from public elementary school students in Jayapura City. This study is descriptive in nature with a laboratory test approach. This study was conducted at the Microbiology Laboratory, Faculty of Health Sciences, Jayapura University of Science and Technology, from March 1, 2025, to June 1, 2025. The population in this study was all students attending public elementary schools in Jayapura City. The samples used in this study were nail clippings from elementary school students, which were examined using the flotation method on samples emulsified in a saturated NaCl solution, followed by microscopic identification. The results showed that of the 32 samples (100%) examined, 6 samples (18.75%) were positive for intestinal worm eggs, including 3 samples (9.37%) of Ascaris lumbricoides eggs (fertile) and Ascaris lumbricoides eggs (unfertile) in 3 samples (9.37%), and negative results without intestinal nematode eggs in 26 samples (81.25%).